Effects of Financial Inclusion and Openness on Banking Stability: Evidence from Developing and Developed Countries - M. Abdi Shalihin; Sugiharso Safuan (Institute for Economic and Social Research, 2021)
This study seeks to contribute to the emerging debate regarding the effects of financial inclusion and openness on banking stability. Panel data from 217 developing and developed countries from 2004 to 2017 showed that financial inclusion did not affect banking stability. However, financial openness significantly affected banking stability in all countries worldwide. Furthermore, the interaction of financial inclusion and openness had a significant positive effect on banking stability in developing and all countries worldwide. This finding indicates that the more funds obtained by banks from the implementation of financial inclusion policy and financial openness policy, the greater the potential for banks to maintain their stability. Therefore, to maintain bank stability, each country needs to synchronize its policies on financial inclusion and financial openness. This finding also contributes to the literature on understanding the essential financial inclusion policies and financial openness to improve bank stability.